Integrated safety analysis of rolapitant with coadministered drugs from phase II/III trials: an assessment of CYP2D6 or BCRP inhibition by rolapitant. (23rd February 2017) - Barbour, S.; Smit, T.; Wang, X.; Powers, D.; Arora, S.; Kansra, V.; Aapro, M.; Herrstedt, J.
Abstract : Background: Rolapitant, a long-acting neurokinin (NK)1 receptor antagonist (RA), has demonstrated efficacy in prevention of chemotherapy-induced nausea and vomiting in patients administered moderately or highly emetogenic chemotherapy. Unlike other NK1 RAs, rolapitant does not inhibit or induce cytochrome P450 (CYP) 3A4, but it does inhibit CYP2D6 and breast cancer resistance protein (BCRP). To analyze potential drug–drug interactions between rolapitant and concomitant medications, this integrated safety analysis of four double-blind, randomized phase II or III studies of rolapitant examined adverse events (AEs) by use versus non-use of drug substrates of CYP2D6 or BCRP. Patients and methods: Patients were randomized to receive either 180 mg oral rolapitant or placebo ∼1–2 h before chemotherapy in combination with a 5-hydroxytryptamine type 3 RA and dexamethasone. Data for treatment-emergent AEs (TEAEs) and treatment-emergent serious AEs (TESAEs) during cycle 1 were pooled across the four studies and summarized in the overall population and by concomitant use/non-use of CYP2D6 or BCRP substrate drugs. Results: In the integrated safety population, 828 of 1294 patients (64%) in the rolapitant group and 840 of 1301 patients (65%) in the control group experienced at least one TEAE. Frequencies of common TEAEs were similar in the rolapitant and control populations. Overall, 53% of patients received CYP2D6 substrate drugs, none of which had a narrow therapeutic index (like thioridazine or pimozide), and 63% received BCRP substrate drugs. When grouped by concomitant use versus non-use of CYP2D6 or BCRP substrate drugs, TEAEs and TESAEs occurred with similar frequency in the rolapitant and control populations. Conclusions: The results of this study support the safety of rolapitant as part of an antiemetic triple-drug regimen in patients receiving emetogenic chemotherapy, including those administered concomitant medications that are substrates of CYP2D6 or BCRP, such as ondansetron, docetaxel, or irinotecan.